Khảo sát khả năng ứng dụng chất hấp thu MnO2 cho phân tích sắc ký khí - Lê, Ngọc Chung (Trường Đại học Đà Lạt, 2012)
Sorption properties of MnO2 have been examined. The results showed that the sorbent of MnO2 can be use to clean-up the chlorophyll and cartene in the sameple extracts and its application for determination of pesticide residue in vegetables by gas chromatography